2017
DOI: 10.1016/j.ejrad.2016.12.009
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of 3D quantitative meniscal and cartilage measures to variation in normal radiographic joint space width—Data from the Osteoarthritis Initiative healthy reference cohort

Abstract: Objective To explore to what extent three-dimensional measures of the meniscus and femorotibial cartilage explain the variation in medial and lateral femorotibial radiographic joint space width (JSW), in healthy men and women. Methods The right knees of 87 Osteoarthritis Initiative healthy reference participants (no symptoms, radiographic signs or risk factors of osteoarthritis; 37 men, 50 women; age 55.0±7.6; BMI 24.4±3.1) were assessed. Quantitative measures of subregional femorotibial cartilage thickness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Quantitative MR imaging was first used in OA research studies to measure cartilage thickness and relaxation characteristics reflecting cartilage composition and microstructure . More recently, quantitative assessment of bone shape, bone marrow edema lesion size, synovial fluid volume, meniscus shape and position, infrapatellar fat pad volume and signal intensity, and muscle bulk have provided important information regarding the association between these structural features and joint pain and the incidence and progression of OA.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative MR imaging was first used in OA research studies to measure cartilage thickness and relaxation characteristics reflecting cartilage composition and microstructure . More recently, quantitative assessment of bone shape, bone marrow edema lesion size, synovial fluid volume, meniscus shape and position, infrapatellar fat pad volume and signal intensity, and muscle bulk have provided important information regarding the association between these structural features and joint pain and the incidence and progression of OA.…”
Section: Introductionmentioning
confidence: 99%
“…Oka et al's study showed that MmJSW had the greatest correlation with the severity of KOA neither lateral joint space nor osteophyte area after adjustment for age and confounding factors. Roth et al [27] found the minimal joint space width reflected a combination of cartilage and meniscal measures, particularly in women. While KL grade was a discrete variable which could not reflect the nuances of the knee joint width, the multiple regression model revealed that the KL grade had no significant difference between the KR group and the KOA group.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that sub-regional femorotibial cartilage thickness predicts knee replacement surgery with an accuracy similar to joint space width (JSW) assessments. In a study performed on 87 healthy subjects using OAI database, correlation between quantitative 3D cartilage and meniscal measures with medial and lateral radiographic JSW was evaluated 46 . Results of their analyses showed a strong relationship between medial minimal JSW and cartilage thickness (in men) as well as cartilage thickness and meniscal measures (in women).…”
Section: Prognosis/predictive Factorsmentioning
confidence: 99%